PENGARUH E-DESIGN WEB DAN E-WORD OF MOUTH TERHADAP E-REPURCHASE DENGAN E-TRUST SEBAGAI VARIABEL INTERVENING PADA WEBSITE LAZADA.CO.ID (STUDI PADA KONSUMEN LAZADA.CO.ID DI SEMARANG) - Faizal Luthfi; Naili Farida (Universitas Diponegoro, 2019)
This research was conducted with the aim to determine the effect of e-design web and e-word of mouth on e-repurchase with e-trust as an intervening variable. This research was conducted on the Lazada.co.id website. The sample of this study amounted to 100 peoples, sampling technique using purposive sampling. Samples are Lazada.co.id website visitors who are more than 17 years old, have made purchases at Lazada at least 2 times and reside in Semarang. The analytical tool used is SPSS 19 for windows with determination, simple and multiple regression analysis, and significance tests (t test and F test). The conclusion of this study is that there is a positive effect of e-design web variables and e-word of mouth on erepurchase through e-trust. (1) e-design web variables have an effect on e-trust, (2) e-word of mouth variables have an effect on e-trust, (3) e-trust variables have an effect on e-repurchase, (4) direct effect e-design web variable on e-repurchase of 0.230, (5) e-word of mouth variable has an effect on e-repurchase of 0.489.